Schools in the media: framing national standardized testing in the Norwegian press, 2004–2018. Issue 4 (4th July 2022) - Camphuijsen, Marjolein K.; Levatino, Antonina
ABSTRACT: In the education sector, media outlets have been increasingly active in reporting on standardized testing. The purpose of this paper is to identify the most recurrent discursive frames used by the Norwegian regional and local press when informing their readers about national standardized testing, and to explore whether differences over time and across geographical localities exist in the pervasiveness of frames. Our analysis is guided by framing theory, and builds on a corpus of 3, 046 articles that focus on national testing, published by 155 Norwegian regional and local newspapers between 2004 and 2018. The analysis identifies four different discursive frames within Norwegian press coverage, namely the frame of 'performance', 'transparency and empowerment', 'misinterpretation and misuse', and 'criticism'. The four frames convey highly distinct causal and normative beliefs and realities about national standardized testing. While the dominance of the frames varies over time and across Norwegian counties, the frame of 'performance' is increasingly pervasive, something that potentially contributes to naturalize performative-oriented reporting and competition in education. The study highlights the importance of systematic media analyses to identify circulating principle beliefs on education, and of not limiting research to national newspapers in order to grasp geographical variation in media coverage.